E-Learning Readiness and Anxiety Levels among Preclinical Medical Students during the COVID-19 Pandemic - Wahyudi, Dery; Pratiwi, Sari Eka; Armyanti, Ita (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: The e-learning readiness measurements were positive, and the level of anxiety was found to be relatively low. Many factors can affect both aspects of e-learning readiness and anxiety among medical students.   Abstract Introduction: The Coronavirus Disease (COVID-19) pandemic has had a significant impact on all sectors, including education. The change from conventional learning systems to e-learning during the pandemic could affect students' mental health, such as the emergence of anxiety. Therefore, this study focused on the relationship between e-learning readiness and anxiety levels, a topic that has not been previously studied in Indonesia. Methods: This was an observational analytic study with a cross-sectional approach. A total of 132 preclinical medical students were chosen through a stratified random sampling technique. Variables were measured using the e-learning readiness (ELR) and Zung Self-Rating Anxiety Scale (SAS) questionnaires. Bivariate analysis using Spearman's rho correlation test was performed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) for Windows version 24.0, with a p<0.05 considered statistically significant. Results: The results showed that the sample was ready to run e-learning but needed minor improvement (55.3%) and had low anxiety levels (87.1%). Spearman's rho correlation test showed no significance, with p=0.545 (p>0.05; r=-0.053). Conclusion: There was no statistically significant relationship between e-learning readiness and anxiety levels of preclinical medical students during the COVID-19 pandemic. These results are crucial for evaluating the ongoing implementation of e-learning as a form of innovation in medical education, even after the COVID-19 pandemic has ended.